RETURNING TO THE PUBLICATION OF DOCTOR OF JURIDICAL SCIENCES, PROFESSOR M.A. SARSEMBAYEV «THE NEED TO IMPROVE STANDARDS OF ILO CONVENTIONS AND THE KAZAKHSTAN LABOR LAW» - Kenzhetayeva Альмира Кадирликызы (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2024)
This article analyzes the article by Professor M.A. Sarsembayev on the topic «The need to improve standards of ILO conventions and the Kazakhstan labor law», which was published in the Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan No. 2 (47) in 2017. In the article Professor M.A. Sarsembayev focuses on the International Labor Organization (ILO) conventions, including the e Convention on Equal treatment and equal opportunities for men and women workers: workers with family responsibilities, adopted in Geneva on the 67-th session of the ILO General Conference on 23 June 1981, the Convention on the Protection of Wages, adopted in Geneva on 32-th session of the General conference of the ILO 1 July 1949, and the ILO Convention on the Minimum Wage Fixing Machinery by 16 June 1928, which are ratified by the Republic of Kazakhstan, with the aim of improving the norms of national labor legislation. The author also identifies shortcomings in these conventions and provides recommendations (translations, new formulations, additional articles, and terms) for their improvement, emphasizing that Kazakhstan, as a party to these conventions, can make proposals for their enhancement through the ILO’s Bureau of Labor Administration. The article also addresses the issue of accession to conventions such as the Convention on Minimum Standards of Social Security (No. 102), the Convention on the Right to Organize and Collective Bargaining in Agriculture (No. 11), the Convention on Compensation for Workmen in Agriculture (No. 12), and the Convention on Medical Care and Sickness Benefits for Workmen in Agriculture (No. 25), considering their significance for the national legal system of Kazakhstan.